Ex-ante demand assessment and willingness to pay for human excreta derived co-compost: Empirical evidence from rural South Africa. (15th February 2023) - Gwara, Simon; Wale, Edilegnaw; Lundhede, Thomas; Jourdain, Damien; Odindo, Alfred
Abstract: Recovering plant nutrients from human excreta streams through circular bioeconomy initiatives like co-composting may offer a cross-sectoral solution to waste management, sanitation, and agriculture. However, the failure of composting innovations is attributed to a lack of a ready market for the compost produced. The current study hypothesizes that improving the desirable attributes of compost to the market through pelletization, fortification, packaging (with labelling), and certification of co-compost could enhance the market demand for co-compost. Socioeconomic variables such as income, religiosity, and environmental attitudes as measured by the new ecological paradigm, were also hypothesized to influence the willingness to pay for co-compost. Based on Lancaster's characteristics demand theory, the efficient Bayesian design, and the discrete choice experiment, we administered a mobile-based survey to 341 rural farmers. The conditional logit, random parameters, and latent class models show that the rural farmers were willing to pay for all the attributes included, especially certification by relevant authorities (ZAR1.70/kg) and fortification with inorganic mineral fertilizers (ZAR1.49/kg). The findings also indicate the influence of income, religiosity, and environmental attitudes on farmers' willingness to pay for co-compost. The results demonstrate the importance of addressing perceived and actual health risk through certification and the complementary role of co-compost in enhancing the agronomic efficiency of chemical fertilizers through fortification in farming systems. Redesigning compost to include the identified attributes could enhance its market appeal. Mainstreaming dissemination strategies and targeting customer segments could improve social acceptance of human excreta-derived compost in agriculture.